Experience report on presential and remote teaching during the COVID-19 pandemic - Milan, Crislaine Sartori Suzana; Manzke , Gabriela (Seven Editora, 2023)
The need for teacher training is a reality among teachers with a bachelor’s degree. Based on this, the present work was developed to describe the experience report of a student of the Pedagogical Training Course for Unlicensed Graduates, about the mandatory teaching internships, drawing a parallel between the internships for reflection. The choice for this report was motivated by seeking to understand the main difficulties and challenges during this period. The activities carried out, from document analysis to conducting classes (face-to-face or virtual) were a unique preparation, the conversations with students, the exchange of experiences with teachers from the technical school, and also with colleagues from the training course, were fundamental lessons learned for preparing for teaching in the classroom. DOI:https://doi.org/10.56238/emerrelcovid19-004